«Na aba da vestidura»: bibliographic essay on the relations between the Portuguese and Ming China - Oliveira, Francisco Roque De (2008)
The contact between Europe and Ming China was mainly made through the Portuguese or their information and merchant networks. As the true eyes of the West in East Asia, at that time the Portuguese produced a number of informative sources about China that are the basis of modern Sinology. In this essay, we shall start by characterizing the nature of Chinese studies in the Portuguese intellectual world. In particular, we will investigate about the existence of a true School of Chinese Studies forged throughout five centuries of continuous relations between Portugal and China. In the second part of the article we shall analyse in detail the two main segments around which are organized the geographical and historical studies on this matter: studies on Macao and those on the broader area of Portuguese-Chinese bilateral relations. We will conclude with a description of the most recent editorial initiatives aimed at the dissemination and critical study of the important Portuguese sources on China written during the sixteenth and the first half of the seventeenth centuries.